Effectiveness of the pilot program correction psychophysical condition of children in the second year of a common educational school - Klyus O. A. (Kharkov National Pedagogical University, 2014)
Purpose: the algorithms have been defined and grounded that contain projecting operations for the formation and implementation of a programme aiming at the correction of psychophysical state of children in the process of physical education during the second year of studying at school. In the investigated was attended by 19 girls and 15 boys second class of experimental group and 30 girls and 30 boys in the control group. Results: it is shown that the increase in body weight of 2.4% in girls and 3.9% boys, increase in body length 14.7% of girls and 11.5% boys, vital capacity of the lungs 22% and 21.8%, respectively, m the muscle strength by dynamometry results brushes right and left hands grew by 142.4 and 94.8%, revealed a significant (from p <0.05 to p <0.001) improved values of all investigated parameters of physical fitness girls and boys. Conclusions: use within one year of the proposed development of 19 girls and 15 boys achieved the much better results in solving tasks than the traditional organization and content of physical education, which are used in the control group.